Semantics of the lexeme “Green” - Turapovna, Israilova Saodat; Tursunaliyevna, Muqaddas Abdurahmonova; Ganiyevna, Nodira Alavutdinova; Islamovna, Nargiz Bekmuxamedova (International Journal of Psychosocial Rehabilitation, 2020)
Study of use of color in the work of fiction and how the described idea is reflected are the topic subjects. The degree of study of color in Uzbek language is studied through classification of words defining colors in the novel, various approaches and situations in use of colors, degrees of equivalence in symmetric and asymmetric relations between the original work and translation.The words defining colors, their use in Uzbek are the subject of the field of concept describing the color symbolism in the original work and translation. The subject was studied in the linguistics of the science of translation, comparative analysis of the conceptual and original and translated text. The novelty of the research is the study of interlingual asymmetry in the use of colors in the translation of the work of fiction.The scientific/theoretical conclusions gained in the process of this research are theoretically and practically important in addressing the colors and problems related to them. The research consists of introduction, three chapters, summary, the list of references and attachment.